Membangun Digital Brand Image Bank Syariah Indonesia : Faktor Penentu Reliability Sistem. - Vidya Sari, Rahmanita; Masjono Muchtar, Ali; Heru Santoso, Stefanus (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
In producing an output, the accounting information system (AIS) will depend on Reliability of AIS System which supports the processes that occur in one or more of the applications used. These processes include computing, sorting, classifying, and summarizing. To guarantee that the process is accurate, precise, and error-free, a reliable accounting information system is needed. The aim of this research is to identify what factors or indicators that  management needs to pay attention to ensure that AIS can produce accurate, precise, and trustworthy output. This research uses a literature study approach, meaning reviewing various literature related to System Reliability and identifying indicators to determine how to measure the reliability of a system. The results are indicators to identify whether the AIS is reliable or not to produce AIS’s output.